Ceramic capacitor grain size measurement method based on ion beam sample preparation imaging

Through the ion beam sample imaging method, the problem of grain-scale measurement accuracy and inefficiency of ceramic capacitors is solved, and higher measurement accuracy and efficiency are achieved, and the integrity of the sample is protected.

CN119438012APending Publication Date: 2025-02-14CHINA ACADEMY OF SPACE TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411842797.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the accuracy and efficiency of grain-scale measurement of ceramic capacitors are inefficient.

Method used

Using an ion beam sample imaging method, the ceramic capacitor to be tested is embedded in the mosaic material, mechanical grinding, physical polishing and ion beam polishing etching are performed, and finally imaging and automatic identification are used to obtain the grain size.

Benefits of technology

It improves the accuracy and efficiency of grain size measurement of ceramic capacitors, protects the integrity of the sample, and enhances the reliability of the results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438012A_ABST
    Figure CN119438012A_ABST
Patent Text Reader

Abstract

According to the ceramic capacitor grain size measurement method based on ion beam sample preparation and imaging, clear grain morphology is obtained by carrying out mechanical grinding and polishing sample preparation and ion beam polishing on a ceramic capacitor sample, so that accurate measurement of the grain size is realized, and the method has important significance in improving the performance and reliability of the ceramic capacitor. The method can be popularized and applied to other fields needing grain size measurement, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for measuring the grain size of a ceramic capacitor based on ion beam sample preparation imaging, and belongs to the technical field of ion beam sample preparation. Background Art

[0002] As an indispensable component in electronic circuits, ceramic capacitors are widely used in power supply filtering, signal coupling, decoupling and other fields due to their small size, high reliability and good frequency characteristics. However, the performance of ceramic capacitors, especially their capacitance, temperature stability, voltage tolerance and life, are closely related to their internal grain size. The uniformity and consistency of the grain size directly affect the dielectric properties and mechanical strength of the capacitor. The uneven grain size may lead to uneven electric field distribution, thereby affecting the breakdown voltage and reliability of the capacitor. In addition, the density and characteristics of the grain boundary also have a significant impact on the leakage current and aging behavior of the capacitor. Therefore, precise control and measurement of the grain size of ceramic capacitors is crucial to improving their performance, reliability and meeting the increasingly stringent requirements of industrial applications.

[0003] Traditional ceramic grain size measurement requires chemical corrosion and thermal corrosion to obtain the microscopic morphology of ceramic grains. Chemical corrosion generally uses a mixed solution of strong acid, such as HF, HCl or HNO3, to treat the surface of the ceramic sample, and forms a morphological phase through the difference in the degree of corrosion of the grain boundary and the grain by the strong acid. Its advantages are simplicity, convenience, high efficiency, and the ability to process a large number of samples at the same time, but it is not effective for powders with smaller particle sizes and powders with strong acid corrosion resistance. Thermal corrosion is to place the sample in a high-temperature furnace and realize the imaging of the grains through the volatilization of grain boundary elements. Because the thermal corrosion conditions of the grain boundary and the grain are significantly different, the volatilization is more thorough when the grain boundary corrosion conditions are reached, and the retention effect of the target analysis object grain is clearer. However, the conditions for thermal corrosion are not easy to explore, and the requirements for equipment are also very high. Summary of the invention

[0004] The technical problem solved by the present invention is: in view of the problems of low accuracy and low efficiency in measuring the grain size of ceramic capacitors in the current prior art, a method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging is proposed.

[0005] The present invention solves the above technical problems by the following technical solutions:

[0006] A method for measuring the grain size of a ceramic capacitor based on ion beam sample preparation and imaging, comprising:

[0007] embedding the ceramic capacitor to be tested in the embedding material;

[0008] Select abrasive paper of corresponding particle size according to the type of embedded material, and mechanically grind the ceramic capacitor to be tested;

[0009] Physically polish the ceramic capacitor to be tested after mechanical grinding;

[0010] The ceramic capacitor to be tested after physical polishing is placed in a vacuum environment, and polished and etched by using an ion beam;

[0011] The effective area surface of the ceramic capacitor to be tested after ion etching and polishing is imaged, and the image file is automatically recognized to obtain the grain size of the ceramic capacitor.

[0012] The embedding material is used to fix the ceramic capacitor to be tested and protect the integrity of the ceramic capacitor to be tested. The embedding material is selected from epoxy resin, acrylic resin or dental tray powder.

[0013] The method of the mechanical grinding is:

[0014] Grinding is performed step by step according to the structure of the ceramic capacitor to be tested. After the effective area of ​​the ceramic capacitor to be tested is traversed and the surface flatness of the effective area of ​​the ceramic capacitor to be tested meets the requirements, solvent samples or cleaning liquid samples are selected according to the material and inlay material of the ceramic capacitor to be tested to ensure that the surface of the effective area of ​​the ceramic capacitor to be tested is clean.

[0015] The method of described physical polishing is:

[0016] Select polishing cloth and polishing liquid that match the material of the ceramic capacitor to be tested, and polish the effective area surface of the ceramic capacitor to be tested after step-by-step grinding;

[0017] When the effective area of ​​the ceramic capacitor to be tested reaches a preset smoothness after the polishing process, the physical polishing process is completed.

[0018] During the physical polishing process, by controlling the polishing pressure and polishing time, after the effective area of ​​the ceramic capacitor to be tested reaches a preset smoothness, excessive polishing is avoided to avoid surface damage to the effective area of ​​the ceramic capacitor to be tested.

[0019] The method of polishing and etching using ion beam is:

[0020] In a vacuum environment, ion beam parameters are set according to the material of the ceramic capacitor to be tested, including ion beam incident angle, ion beam voltage, and incident time; when the effective area of ​​the ceramic capacitor to be tested is evenly polished, the ion beam polishing and etching is stopped;

[0021] The uniform polishing effect is judged by the presence or absence of obvious scratches or mechanical damage.

[0022] The number of rounds of polishing and etching using ion beam is designed to be two rounds. After uniform polishing is achieved, the ion beam polishing and etching is completed if the surface grain boundary of the ceramic capacitor to be tested is clear and there is no metal electrode expansion blocking it.

[0023] The method for automatically identifying image files is:

[0024] A scanning electron microscope is used to image the surface of the effective area of ​​the ceramic capacitor to be tested after ion etching and polishing, and a grain morphology image file is obtained. The grain morphology image file is recognized by external image recognition software to obtain all grain sizes on the surface of the effective area, and all grain sizes are statistically analyzed to calculate the average and standard deviation of the grain sizes.

[0025] The average value and standard deviation of the grain size are used to evaluate the uniformity and consistency of the surface grains of the ceramic capacitor to be tested after the preparation and polishing process.

[0026] The ion beam polishing etching is achieved by using an ion polishing machine to generate an ion beam.

[0027] The advantages of the present invention compared with the prior art are:

[0028] (1) The present invention provides a method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging technology avoids chemical or thermal damage to the sample, reduces deformation and structural damage to the sample during the sample preparation process, and maintains the original state of the sample. Compared with the traditional multi-step corrosion process, ion beam polishing can significantly reduce sample preparation time and improve work efficiency. At the same time, the ion beam polishing process can be automatically controlled by computer, reducing the uncertainty of manual operation and improving the consistency and repeatability of sample preparation. This method is not only suitable for ceramic capacitors, but can also be extended to other ceramic material fields that require grain size measurement, and has broad application prospects;

[0029] (2) The present invention not only improves the accuracy and efficiency of the grain size measurement of ceramic capacitors, but also protects the integrity of the samples and enhances the reliability of the results. It has important practical application value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A flow chart of the grain size measurement method provided by the present invention;

[0031] Figure 2 The morphology diagram for measuring the ceramic grain size obtained in the implementation case provided by the present invention. DETAILED DESCRIPTION

[0032] A method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging, which obtains a clear grain morphology by mechanical grinding and polishing and ion beam polishing of ceramic capacitor samples, thereby achieving accurate measurement of grain size. This is of great significance for improving the performance and reliability of ceramic capacitors, can be promoted and applied to other fields that require grain size measurement, and has broad industrial application prospects.

[0033] The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging includes the following steps:

[0034] embedding the ceramic capacitor to be tested in the embedding material;

[0035] Select abrasive paper of corresponding particle size according to the type of embedded material, and mechanically grind the ceramic capacitor to be tested;

[0036] Physically polish the ceramic capacitor to be tested after mechanical grinding;

[0037] The ceramic capacitor to be tested after physical polishing is placed in a vacuum environment, and polished and etched by using an ion beam;

[0038] The effective area surface of the ceramic capacitor to be tested after ion etching and polishing is imaged, and the image file is automatically recognized to obtain the grain size of the ceramic capacitor.

[0039] The inlay material is used to fix the ceramic capacitor to be tested and protect the integrity of the ceramic capacitor to be tested. The inlay material is selected from epoxy resin, acrylic resin or dental tray powder;

[0040] The method of mechanical grinding is:

[0041] Grinding is performed step by step according to the structure of the ceramic capacitor to be tested. After the effective area of ​​the ceramic capacitor to be tested is traversed and the surface flatness of the effective area of ​​the ceramic capacitor to be tested meets the requirements, solvent samples or cleaning liquid samples are selected according to the material and inlay material of the ceramic capacitor to be tested to ensure that the surface of the effective area of ​​the ceramic capacitor to be tested is clean.

[0042] The methods of physical polishing are:

[0043] Select polishing cloth and polishing liquid that match the material of the ceramic capacitor to be tested, and polish the effective area surface of the ceramic capacitor to be tested after step-by-step grinding;

[0044] When the effective area of ​​the ceramic capacitor to be tested reaches a preset smoothness after the polishing process, the physical polishing process is completed.

[0045] During the physical polishing process, by controlling the polishing pressure and polishing time, after the effective area of ​​the ceramic capacitor to be tested reaches a preset smoothness, excessive polishing is avoided to avoid surface damage to the effective area of ​​the ceramic capacitor to be tested.

[0046] The method of polishing and etching using ion beam is:

[0047] In a vacuum environment, ion beam parameters are set according to the material of the ceramic capacitor to be tested, including ion beam incident angle, ion beam voltage, and incident time; when the effective area of ​​the ceramic capacitor to be tested is evenly polished, the ion beam polishing and etching is stopped;

[0048] Uniform polishing is judged by the good microscopic flatness and grain morphology consistency of each effective area under scanning electron microscope inspection, and the absence of obvious scratches or mechanical damage.

[0049] The number of rounds of polishing and etching using ion beam is designed to be two rounds. After uniform polishing is achieved, the ion beam polishing and etching is completed if the surface grain boundary of the ceramic capacitor to be tested is clear and there is no metal electrode expansion blocking it.

[0050] The method for automatically identifying image files is:

[0051] A scanning electron microscope is used to image the surface of the effective area of ​​the ceramic capacitor to be tested after ion etching and polishing, and a grain morphology image file is obtained. The grain morphology image file is recognized by external image recognition software to obtain all grain sizes on the surface of the effective area, and all grain sizes are statistically analyzed to calculate the average and standard deviation of the grain sizes.

[0052] The average value and standard deviation of the grain size are used to evaluate the uniformity and consistency of the surface grains of the ceramic capacitor to be tested after the preparation and polishing process.

[0053] The following is further described in conjunction with the accompanying drawings and preferred embodiments of the specification:

[0054] In the current embodiment, the following detailed steps are taken:

[0055] A. Sample Mounting Preparation

[0056] Ceramic capacitor samples are embedded in an appropriate mounting material to secure the sample and protect its structural integrity.

[0057] This ensures that the sample is not damaged during the mounting process and facilitates subsequent grinding and polishing steps.

[0058] B. Mechanical grinding

[0059] Using a series of grinding papers of different grits, the mounted samples were mechanically ground step by step, from coarse grinding to fine grinding, gradually grinding to the effective area of ​​the ceramic body.

[0060] After each grinding step, wash the sample with an appropriate solvent or cleaning solution to remove the residue of the grinding media and sample debris, ensuring a clean surface to prevent these debris from damaging the sample in subsequent steps.

[0061] C. Physical polishing

[0062] After mechanical grinding, physical polishing technology is used to further refine the sample surface, using polishing cloth and polishing liquid to polish the sample to achieve mirror-like smoothness.

[0063] During the physical polishing process, the polishing pressure and polishing time should be strictly controlled to avoid excessive polishing that may cause damage to the sample surface.

[0064] D. Ion etching polishing

[0065] In a high vacuum environment, an ion beam is used to polish and etch the sample surface. Appropriate ion beam parameters, including ion beam incident angle, voltage, and time, are selected to achieve uniform polishing of the sample surface.

[0066] E. Grain size measurement

[0067] Scanning electron microscopy (SEM) was used to perform high-resolution imaging of the sample surface after ion etching and polishing to obtain clear grain morphology images.

[0068] Image analysis software is used to process and analyze the acquired images, automatically identify grain boundaries, and measure grain sizes.

[0069] like Figure 1 As shown, the embodiment:

[0070] Step 1: Sample Mounting Preparation

[0071] The MLCC samples were embedded and potted with epoxy resin to facilitate subsequent mechanical grinding and ion etching polishing.

[0072] Step 2: Mechanical grinding

[0073] Diamond sandpaper of different grits (120#, 600#, 1200#, 2500#) was used to grind the sample mechanically step by step until the sample was ground to the effective area of ​​the ceramic body and the sample surface reached the required flatness.

[0074] Step 3: Physical Polishing

[0075] Physical polishing technology was used to further polish the sample using polishing cloth and polishing liquid to achieve mirror-like smoothness. During the physical polishing process, the polishing pressure was controlled to 10N and the polishing time was 60s to avoid excessive polishing that would cause damage to the sample surface.

[0076] Step 4: Ion Etching and Polishing

[0077] The sample surface was polished by ion beam etching in two rounds using an ion polisher. The voltage of the first round was set to 6 kV, the polishing time was 30 min, and the ion beam angle was 4°; the voltage of the second round was set to 4 kV, the polishing time was 20 min, and the ion beam angle was 4°. After ion beam polishing, the grain boundaries on the sample surface were clearly visible, without any metal electrode expansion or obstruction. The results were judged based on the good microscopic flatness and grain morphology consistency of each effective area under scanning electron microscope inspection, and no obvious scratches or mechanical damage.

[0078] Step 5: Grain size measurement

[0079] SEM imaging was performed on the samples after ion etching and polishing, and then the image analysis software was used to measure and statistically analyze the grain size to evaluate the uniformity and consistency of the grain size. The measurement results are as follows: Figure 2 shown.

[0080] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

[0081] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. A method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging, characterized in that include: embedding the ceramic capacitor to be tested in the embedding material; Select abrasive paper of corresponding particle size according to the type of embedded material, and mechanically grind the ceramic capacitor to be tested; Physically polish the ceramic capacitor to be tested after mechanical grinding; The ceramic capacitor to be tested after physical polishing is placed in a vacuum environment, and polished and etched by using an ion beam; The effective area surface of the ceramic capacitor to be tested after ion etching and polishing is imaged, and the image file is automatically recognized to obtain the grain size of the ceramic capacitor.

2. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 1, characterized in that: The embedding material is used to fix the ceramic capacitor to be tested and protect the integrity of the ceramic capacitor to be tested. The embedding material is selected from epoxy resin, acrylic resin or dental tray powder.

3. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 1, characterized in that: The method of the mechanical grinding is: Grinding is performed step by step according to the structure of the ceramic capacitor to be tested. After the effective area of ​​the ceramic capacitor to be tested is traversed and the surface flatness of the effective area of ​​the ceramic capacitor to be tested meets the requirements, solvent samples or cleaning liquid samples are selected according to the material and inlay material of the ceramic capacitor to be tested to ensure that the surface of the effective area of ​​the ceramic capacitor to be tested is clean.

4. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 1, characterized in that: The method of described physical polishing is: Select polishing cloth and polishing liquid that match the material of the ceramic capacitor to be tested, and polish the effective area surface of the ceramic capacitor to be tested after step-by-step grinding; When the effective area of ​​the ceramic capacitor to be tested reaches a preset smoothness after the polishing process, the physical polishing process is completed.

5. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 4, characterized in that: During the physical polishing process, by controlling the polishing pressure and polishing time, after the effective area of ​​the ceramic capacitor to be tested reaches a preset smoothness, excessive polishing is avoided to avoid surface damage to the effective area of ​​the ceramic capacitor to be tested.

6. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 1, characterized in that: The method of polishing and etching using ion beam is: In a vacuum environment, ion beam parameters are set according to the material of the ceramic capacitor to be tested, including ion beam incident angle, ion beam voltage, and incident time; when the effective area of ​​the ceramic capacitor to be tested is evenly polished, the ion beam polishing and etching is stopped; The uniform polishing effect is judged by the presence or absence of obvious scratches or mechanical damage.

7. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 6, characterized in that: The number of rounds of polishing and etching using ion beam is designed to be two rounds. After uniform polishing is achieved, the ion beam polishing and etching is completed if the surface grain boundary of the ceramic capacitor to be tested is clear and there is no metal electrode expansion blocking it.

8. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 1, characterized in that: The method for automatically identifying image files is: A scanning electron microscope is used to image the surface of the effective area of ​​the ceramic capacitor to be tested after ion etching and polishing, and a grain morphology image file is obtained. The grain morphology image file is recognized by external image recognition software to obtain all grain sizes on the surface of the effective area, and all grain sizes are statistically analyzed to calculate the average and standard deviation of the grain sizes.

9. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 8, characterized in that: The average value and standard deviation of the grain size are used to evaluate the uniformity and consistency of the surface grains of the ceramic capacitor to be tested after the preparation and polishing process.

10. The method for measuring the grain size of ceramic capacitors based on ion beam sample preparation and imaging according to claim 7, characterized in that: The ion beam polishing etching is achieved by using an ion polishing machine to generate an ion beam.

Citation Information

Patent Citations

  • Method for observing TSV (through-silicon-via) copper crystalline grains

    CN103472265A

  • Sample preparation method for rapidly obtaining silicon carbide ceramic grain information and sample analysis and determination method

    CN110567998A

  • Method for rapidly obtaining grain size of nickel electrode ceramic capacitor

    CN113092200A

  • Manufacture of ceramic circuit board

    JP1993024959A

  • Method and device for measuring grain size of powder

    JP1995092074A